PERDAGANGAN DAN EKONOMI DI SULAWESI SELATAN, PADA TAHUN 1900-an SAMPAI DENGAN 1930-an - Nur, Nahdia; Purwanto, Bambang; Suryo, Djoko (JURNAL ILMU BUDAYA, 2016)
This South part of Sulawesi has very important function in commodity trading. In such trading, there are linked connections that have produced trade contact to the outside world as well as created important traf- fic, particularly in Makassar. This commerce connection expansion politic succeed in realizing the goal to put Makassar as the only trading central in this area. Traders and seamen of Bugis, Makassar, Selayar, Malay and Portugese who carry out commercial voyage have made Makassar as transit harbor and pro- duction market. Makassar appears as main port in trading connection with production region and making connection with other trading ports located in east, south, west and north parts. The happening political growth has forced the Dutch Government to reform its economical policy, partic- ularly in putting Makassar Harbor as one of free harbor under the Dutch Government control. The Gov- ernment also able to extend its influence towards the self-governing monarchies in this region, therefore it might prevent the wish of other countries that are active in conducting trading to South East Asia to make authority connection with them. The Government is implementing the free harbor policy in order to at- tract and centralize trading acitivities in south part. The Dutch Government also regularly investigates and handles commodity prices in Makassar under agri- culture consultants supervision, such as rice, coffee, corn, cotton, resin, rattan, etc. These prices are ad- dressed to local and available authorities as notification concerning market price. This matter points at central government involvement and now there are a lot of commodity products, so that the Government is forced to be involved by implementing prohibition upon commodity import, particularly rice. Keywords: trading, harbor, commodity, economy